Association Between Allometric Body Shape Indices and Osteoporosis in Postmenopausal Women: A Cross-Sectional Study from NHANES - Zhao S; Pan X (International Journal of Women's Health)
Songfeng Zhao,1,2 Xin Pan1,2 1Department of Endocrinology, The First People’s Hospital of Xiaoshan District, Hangzhou, Zhejiang, People’s Republic of China; 2Department of Endocrinology, Xiaoshan Affiliated Hospital of Wenzhou Medical University, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Xin Pan, Department of Endocrinology, The First People’s Hospital of Xiaoshan District, No. 199 South Shixin Road, Xiaoshan District, Hangzhou, Zhejiang, People’s Republic of China, Tel +86-0571-83807971, Email 344132702@qq.comBackground: Osteoporosis is a common health concern in postmenopausal women. Obesity, commonly assessed using body mass index (BMI), may have a protective effect on osteoporosis in postmenopausal women. As BMI is limited to the distinguishing fat accumulation, the study aimed to explore the association between allometric body shape indices [including a body shape index (ABSI), hip index, (HI), and waist–hip index (WHI)] and osteoporosis in postmenopausal women.Methods: Postmenopausal women aged > 50 years in the National Health and Nutrition Examination Survey from 2017 through 2020 (revised to 01/2017 through 12/2020) were included. Potential covariates were selected using the univariate logistic regression models. The association between allometric body shape indices and osteoporosis was explored using weighted univariate and multivariate logistic regression models, with results presented as odds ratios (ORs) and 95% confidence intervals (CIs). The association was further explored in different age and BMI populations. Area under the curve (AUC) analysis was conducted to evaluate the predictive performance of WHI.Results: In total, 810 postmenopausal women aged > 50 years were included. Among them, 597 (73.70%) women have osteoporosis. WHI ≥ 0.094 (OR = 2.07, 95% CI: 1.14– 3.78) was associated with higher odds of osteoporosis in postmenopausal women. BMI ≥ 30 kg/m2 (OR = 0.23, 95% CI: 0.11– 0.50) was also related to decreased odds of osteoporosis. ABSI ≥ 85.74 was related to a higher incidence of osteoporosis in women aged ≥ 70 years (OR = 4.18, 95% CI: 1.22– 14.35) and BMI ≥ 30 kg/m2 (OR = 4.25, 95% CI: 1.82– 9.95). The WHI has a better predictive performance with an AUC of 0.656 (95% CI: 0.613– 0.699) than the waist–hip ratio.Conclusion: Higher WHI was associated with an increased incidence of osteoporosis in postmenopausal women. Higher ABSI was related to a higher incidence of osteoporosis in women aged ≥ 70 years and those with a BMI ≥ 30 kg/m2. WHI could predict the incidence of osteoporosis in postmenopausal women.Keywords: osteoporosis, postmenopausal, a body shape index, hip index, waist–hip index